2022
DOI: 10.3390/plants11131756
|View full text |Cite
|
Sign up to set email alerts
|

Metabolome Profiling: A Breeding Prediction Tool for Legume Performance under Biotic Stress Conditions

Abstract: Legume crops such as common bean, pea, alfalfa, cowpea, peanut, soybean and others contribute significantly to the diet of both humans and animals. They are also important in the improvement of cropping systems that employ rotation and fix atmospheric nitrogen. Biotic stresses hinder the production of leguminous crops, significantly limiting their yield potential. There is a need to understand the molecular and biochemical mechanisms involved in the response of these crops to biotic stressors. Simultaneous exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 109 publications
2
7
0
Order By: Relevance
“…Metabolites are products that play major roles in plant response to environmental stress conditions. Currently, there is limited knowledge on metabolites involved in resistance against an array of fungal and bacterial pathogens in legumes ( Makhumbila et al, 2022 ). In this study, an untargeted metabolome profiling of two common bean genotypes Teebus-RR-1 and Golden Gate Wax were investigated for their response to race 1 and 3 U. appendiculatus infections at different time-points (14 and 21 days).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolites are products that play major roles in plant response to environmental stress conditions. Currently, there is limited knowledge on metabolites involved in resistance against an array of fungal and bacterial pathogens in legumes ( Makhumbila et al, 2022 ). In this study, an untargeted metabolome profiling of two common bean genotypes Teebus-RR-1 and Golden Gate Wax were investigated for their response to race 1 and 3 U. appendiculatus infections at different time-points (14 and 21 days).…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomic techniques have played a vital role in aiding researchers to identify significant metabolites that contribute to legume improvement ( Ramalingam et al, 2015 ). Profiling of metabolites using LC-MS techniques has been widely utilised to evaluate legume performance under disease pressure ( Makhumbila et al, 2022 ). In a recent study, common bean infected with Fusarium solani significantly enriched biosynthesis of amino acids, flavonoid biosynthesis, purine metabolism and other pathways as a pathogen adaptation strategy ( Chen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Infected common bean seedlings responded with modifications to their cell walls, the generation of reactive oxygen species, and a synergistic hormone-driven defense response. The study also found that infected plants induced energy metabolism, nitrogen mobilization, accumulation of sugars, and arginine and proline metabolism (Chen et al, 2020;Makhumbila et al, 2022). Reliable software tools such as GCMS, LC-MS, and NMR are required to analyze the vast amounts of data generated by metabolomic technologies.…”
Section: Methanol Leavesmentioning
confidence: 99%
“…It highlights the expressions and changes of metabolites, as well as their interactions and resulting phenotypic traits in plants subjected to harsh environmental conditions. Under such stress, plants must adapt their metabolomic pathways to maintain metabolic homeostasis, a process referred to as acclimation (Joshi et al, 2021;Makhumbila et al, 2022). Chen et al (2020) studied the metabolomic profile of common bean and identified major findings related to amino acids, flavonoids, isoflavonoids, purines, and proline metabolism.…”
Section: Methanol Leavesmentioning
confidence: 99%
“…The review of Makhumbila et al [ 6 ] provides a progress update on metabolomic studies of legumes in response to different biotic stresses. In their contribution, metabolome annotation and data analysis platforms are discussed together with future perspectives.…”
mentioning
confidence: 99%